Non‐linear Dynamics of Electrical Machines: A Kind of Electro‐Mechanical Sommerfeld Effect?. Issue 1 (17th December 2018) - Boy, Felix; Hetzler, Hartmut
Abstract: Electrical machines in modern applications, as for example in electric mobility, are operated at high and rapidly changing rotational speeds. Under such conditions, lateral rotor oscillations due to unbalanced magnetic pull and modified flux linkage may affect the torque and rotational motion and thus the operational reliability. Such a scenario, which shows certain similarities to the SOMMERFELD‐effect in classical rotordynamics, is analysed within this paper using a computationally fast model, based on LAGRANGE‐MAXWELL equations and the permeance harmonic method.